1994
DOI: 10.1002/mrd.1080370415
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gonadotropins upon the incidence and kinetics of meiotic maturation of macaque oocytes in vitro

Abstract: The specific aim of this study was to determine the effects of gonadotropins in vitro upon the incidence of and precise time interval to germinal vesicle breakdown (GVB) and extrusion of the first polar body (PB1) in oocytes from nonstimulated rhesus monkeys. Cumulus-enclod germinal vesicle (GV) stage oocytes from 10 normal, cycling rhesus monkeys in the follicular phase of the menstrual cycle were cultured with either: (1) 1.0 micrograms/ml human follicle-stimulating hormone (hFSH), (2) 10 micrograms/ml human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…In oocytes from untreated marmosets, the competence to resume and complete meiosis and the time course of nuclear progression in vitro was highly dependent on the size of the follicle from which the oocyte originated. Marmoset oocytes from intermediatesized antral follicles exhibit a notably higher capacity to meiotically mature in vitro (90-100%, [7] and present study) than oocytes from macaques (15-56%, [10,[26][27][28]) and humans (17-68%, [12,[29][30][31][32]). In unprimed marmosets, oocytes from the smallest antral follicles have a lower meiotic potential than oocytes from larger antral follicles, and those that are able to mature do so more slowly.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In oocytes from untreated marmosets, the competence to resume and complete meiosis and the time course of nuclear progression in vitro was highly dependent on the size of the follicle from which the oocyte originated. Marmoset oocytes from intermediatesized antral follicles exhibit a notably higher capacity to meiotically mature in vitro (90-100%, [7] and present study) than oocytes from macaques (15-56%, [10,[26][27][28]) and humans (17-68%, [12,[29][30][31][32]). In unprimed marmosets, oocytes from the smallest antral follicles have a lower meiotic potential than oocytes from larger antral follicles, and those that are able to mature do so more slowly.…”
Section: Discussionmentioning
confidence: 55%
“…The present study has shown that marmoset oocytes require appreciably less time in vitro to mature (20-24 h) than do oocytes from rhesus monkeys (30-34 h, [27,46]) and humans (36-47 h, [32,47]); this time period is more comparable to that required by oocytes of domestic ungulates (16-27 h, [45,[48][49][50][51]). Oocytes from the largest follicles (> 1.4 mm; found only in FSH-primed marmosets) presented an anomaly in the relationship between follicle size and the timing of meiotic maturation in that they tended to mature more slowly than those from smaller follicles, although this was nonsignificant because of the small numbers of oocytes in this class.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Both human and macaque oocytes isolated from large antral follicle resume spontaneous meiosis [52,[71][72][73][74]. In nonhuman primates [42,60,69,70], as in women [75,76], gonadotropin priming in vivo has been shown to increase the number of oocytes collected and improve their maturation as well as to enhance the embryonic competence. In contrast, oocytes from small follicles unresponsive to an ovulatory gonadotropin surge or from dissected ovaries collected at unknown stages of the menstrual cycle, presumably from small follicles not exposed to gonadotropins, are also used in human IVM, but their competence is lower [29,31,32,[77][78][79][80][81].…”
Section: Discussionmentioning
confidence: 99%
“…This source of the COCs is distinct from those in previous reports using both nonhuman primates and women. Most prior studies evaluating IVM in nonhuman primate models used oocytes from large antral follicles of monkeys primed with FSH for 6-7 days [42,60,69,70]. Both human and macaque oocytes isolated from large antral follicle resume spontaneous meiosis [52,[71][72][73][74].…”
Section: Discussionmentioning
confidence: 99%